Basic requirements for implementation of total quality management in Centers of Emergency Medical Services in Iran according EFQM model - Abedsaeedi, zhila; Mozafari, Mosaieb; Pazargadi, Mehrnoosh; Alavi majd, Hamid (Advances in Nursing & Midwifery, 2012)
Basic requirements for implementation of total quality management in Centers of Emergency Medical Services in Iran according EFQM model Abedsaeedi, Z1. (PhD); Mozafari,M2.*((PhD); Pazargadi,M.3 (PhD); Alavi majd, H.4 (PhD) 1. Assistant Professor, Dept of Medical Surgical, Faculty of Nursing & Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran 2. PhD Student, Dept of Nursing, Faculty of Nursing & Midwifery, Shahid Beheshti University of Medical Sciences, Lecturer, Ilam University of Medical Sciences, Ilam, Iran 3. Associate Professor, Dept. of Management, Faculty of Nursing & Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran 4. Associate Professor, Dept. of Biostatistics. Faculty of Paramedicine, Shahid Beheshti University of Medical Sciences, Tehran, Iran Abstract Background and aim Successful implementation of TQM requires a committed leadership, customer – based approaches, process management, efficient communication, knowledge management, empowerment and involvement of staff and an organizational culture for continuous quality improvement. The aim of this study was to assess basic requirements for implementation TQM in Centers of Emergency Medical Services in Iran according EFQM model. Materials and methods In this descriptive study, all of operational and official stations of Medical Emergency services in Ilam, Bushehr, Mazandaran, Ardebil, West Azerbaijan and Yazd province, one half of operational stations in city of Tehran, Sistan–Baluchestan, Khorasan-razavi and Isfahan, were included. All senior managers and personnel of these centers and a random sample of 3246 customers who have received care during the last 6 months were selected. By using a 189 –item’s rating scale and 4 questionnaires; leadership style, job and patients satisfaction and state of organizational empowering, according to 5 enabler criteria, from EFQM model was assessed. Validity of instruments by measuring content validity and reliability by internal consistency and test-retest confirmed. Descriptive and inferential statistics used for analyzing data. Findings The overall mean score was 168.4±34.6 out of 500; therefore, the selected divisions were labeled as drifters organizations which were in early stage of quality improvement road. In comparison, the Tehran, Isfahan and Khorasan-razavi centers with more score labeled as improver’s organizations. At the entire, leadership criterion obtained minimum (26.6%) and people criterion obtained maximum (39%) mean scores. Conclusion Results showed that enabler criteria of the EMS centers in Iran need to reinforcement. It is essential enhancing the knowledge and attitude of managers and personnel about quality improvement principles. Additionally, establishing the management by process, creating customer focused approach and culture of continuous improvement, empowering employees and constituting quality circles are appropriate interventions that should be considered Keywords: European Foundation for Quality Management (EFQM), Total Quality Management (TQM), Center for Management of Accidents and Emergencies, Emergency System, Enabler criteria. *Corresponding Author: Mosayeb, Mozafari. Dept of Nursing. Faculty of Nursing & Midwifery, Ilam University of Medical Sciences, Ilam, Iran, Banganjab. E-mail: Mozafaric@yahoo.com